PELAYANAN PRIMA PADA PAKET UMRAH DI PT. ANNAJWA TOUR & TRAVEL PEKANBARU - Nasution, Muna Rofiyana; Sulistyani, Andri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
Umrah is one of the major acts of worship in Islam which is carried out in the Holy Land, namely Mecca. Umrah means performing tawaf at the Kaaba and sa'i between Shofa and Marwah. Indonesia is one of the countries that has the largest Muslim population in the world, who perform the Hajj and Umrah every year. Thus, to make your pilgrimage easier, you can use an Umrah travel agency. One of the Umrah travel agents in Pekanbaru is PT. Annajwa Tour & Travel can make it easier for people to carry out the Umrah pilgrimage without any obstacles. If they want to carry out the Umrah pilgrimage then people can use the Umrah hajj travel services available at PT. Annajwa Tour & Travel. This research aims to find out excellent service in Umrah packages at PT. Annajwa Tour and Travel. This research uses qualitative methods to explain the situation that occurred by collecting data and information in the field. The sources of informants in this research were the Head of the Office and Umrah pilgrims at PT. Annajwa Tour and Travel. In this research, the data collection techniques used were observation, interviews and documentation. The results of this research reveal excellent service at PT. Annajwa is in accordance with the indicators of Excellent Service, namely ability, attitude, appearance, attention, action, responsibility. Keywords: travel, service, umrah